Inventory of Pests and Diseases of Figure-Eight Kaffir Lime (Citrus hystrix D.C.) Plants on Sandy Land - Muhammad Aksan; Firman; Jusman Tang; Muhammad Faisal Saade (Universitas Muhammadiyah Enrekang, 2026)
This study aimed to identify the diversity of pests and diseases associated with kaffir lime (Citrus hystrix D.C.) cultivated at PT Al Fatih Porang, Sidenreng Rappang Regency, on dry sandy land. The research was conducted using a survey method during the generative growth stage before the plants entered the senescence phase. A total of 200 sample plants were selected from a population of 1,020 plants using a diagonal sampling method. Insect pests were documented through field photography and identified based on their morphological characteristics, while diseases were identified based on the visual symptoms observed on the plants. The results revealed the presence of four dominant insect pest species and four dominant diseases associated with kaffir lime plants in the study area. The occurrence of these pests and diseases indicates that the pest complex associated with kaffir lime is relatively diverse and shares characteristics commonly found in other citrus species. These findings provide a basis for developing effective pest and disease management strategies for kaffir lime cultivation on dry sandy soils